Boosted magneto-photothermal therapy of cancer cells by carboxylated carbon-coated plasmonic satellite/magnetic core nanoplatforms - Yingran Shen; Kai Feng; Yanze Yin; Bei Yang; Hao Wang; Guang Yang; Jie Cai (Results in Engineering)
Hybrid plasmonic-magnetic nanoparticles (NPs) can mediate tumors through the magneto-photothermal therapy, gaining rising attention in the treatment of oncology. Herein, carboxylated carbon coated plasmonic satellite/magnetic core NPs were successfully fabricated by a pulsed laser ablation in solution. Plasmonic element (Au, Pd, Ag and Cu), shell thickness (i.e., 1–2 layers over Fe2O3 core and 1–2 layers over Au satellite) and plasmonic/magnetic composition were systematically tailored to achieve optimal plasmonic/magnetic properties. These designed NPs were applied as heat generators as functions of NP concentrations, laser power densities and magnetic field intensities. Carboxylated shells facilitated good colloidal stability and cellular uptake of NPs. Carbon coated plasmonic satellite/magnetic core NPs exhibited excellent capability (66.1–193.6 mM−1·s−1) of magnetic resonance imaging for lung tumor visually in vivo. Cancer cells were killed in 300 s in vitro by enhanced the temperature of lung tumor rapidly to 55 °C within 100 s with combined exposure dual modalities including laser radiation of 0.75 W/cm2 (785 nm) and magnetic field of 400 Oe. Carbon coated plasmonic satellite/magnetic core NPs present good biocompatibility in multiple organs. This work provided a versatile strategy for fabricating core/satellite theranostic nanoprobes with rationally multimodal imaging and therapeutic functionalities.